Burning mouth syndrome and Reflux Disease: relationship and clinical implications: Clinical implications of BMS and reflux - Russo, Michele; Crafa, Pellegrino; Franceschi, Marilisa; Rodriguez-Castro, Kryssia Isabel; Franzoni, Lorella; Guglielmetti, Simone; Fiore, Walter; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: An association between reflux and burning mouth syndrome (BMS) has been proposed. Aims of this study were: 1) to investigate the frequency of BMS in a sample of GERD patients; 2) to measure G17, in a sample of BMS patients; 3) to assess the efficacy of different therapeutical schedules for GERD in BMS patients. Methods: We divided the study in 3 main steps. In step one, we analyzed 500 consecutive GERD patients’ type and frequency of extraesophageal manifestations including BMS. In step two, we collected 124 consecutive BMS patients’ symptoms and G17. In step three, we evaluate the efficacy of 3 different drugs on BMS. Results: In step one, 204 patients complained heartburn; 31 globus pharyngeus; 52 chronic cough; 54 pharyngitis; 31 postnasal drip; 56 burning mouth symptoms; 34 noncardiac chest pain; 17 asthma and 21 sleep apnea. In step two, 29 patients had G17 ≤ 1 pg/L; 64 patients between 1 and 3; and 31 patients ≥ 3. In step three, 49 patients reported slight benefit with PPI, 75 no benefit. 61 patients reported slight benefit with sodium alginate and sodium bicarbonate, 63 no benefit. 23 reported an almost complete remission with HYCHSA, 26 slight benefit, 33 no benefit. Conclusions: Prevalence of BMS in GERD patients was similar to that reported for chronic chough and pharyngitis. Low levels of G17 were found in the majority of BMS patients. Finally, we observed a greater benefit from barrier drugs therapy than from PPI therapy in BMS patients. (www.actabiomedica.it)